Fenestration of bone flap during interval autologous cranioplasty - Nguyen, Ha Son (Surg Neurol Int, 2015)
BACKGROUND: Symptomatic extra-axial fluid may complicate cranioplasty and require urgent evacuation. Fenestration (F) of the bone flap may encourage extra-axial fluid absorption; however, literature has not explored this technique. METHODS: Thirty-two consecutive patients who underwent interval autologous cranioplasty were divided into two groups: Fenestration, n = 24, and no fenestration (NF), n = 8. Fenestration involves placement of twist-drill holes 1–2 cm apart throughout the bone flap. Clinical data (age, sex, underlying pathology for cranioplasty, history of antiplatelet/anticoagulation [A/A], presence of drains, and length of Intensive Care Unit [ICU] stay) were collected. Postoperative volume and midline shift (MLS) were measured. Univariate analysis was performed for continuous variables; Fisher's exact test was performed for categorical variables. RESULTS: For postoperative volume, NF group exhibited 33.745 ± 48.701 cm(3); F group exhibited 20.832 ± 26.103 cm(3) (P = 0.351). For MLS, NF group exhibited 3.055 ± 0.472 mm; F group exhibited 0.75 ± 0.677 mm (P = 0.009). MLS for the NF group subset with drains was 1.235 ± 0.566 mm, (P = 0.587 when compared to F group). For ICU length of stay, NF group exhibited 1.958 ± 1.732 days; F group exhibited 2.290 ± 0.835 days (P = 0.720). In NF group, for patients with no A/A, no drain exhibited MLS 4.00 ± 0.677 mm while a drain exhibited 1.845 ± 0.605 mm (P = 0.025); with A/A, no drain exhibited 5.75 ± 1.353 mm while a drain exhibited 0.625 ± 0.957 (P = 0.005). Four NF patients required reoperation compared to zero F patients (P = 0.550). CONCLUSION: Presumably, fenestrations augment surface area for extra-axial fluid absorption through the bone flap. Our results, regarding MLS and postoperative volume, provide support for this concept. Accordingly, bone flap fenestration has the potential to reduce extra-axial fluid accumulation.